2016
DOI: 10.1007/s11701-016-0599-3
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted video endoscopic inguinal lymphadenectomy for melanoma

Abstract: Inguinal lymphadenectomy is the indicated procedure in the regional lymph node management for patients with lower limb melanoma and positive nodes. This procedure is commonly associated with surgical site complications. Video endoscopic inguinal lymphadenectomy is a minimally invasive alternative with oncological principles and lower wound-related morbidity. Incorporation of robotic surgery with optimal vision and great maneuverability would offer great advantages. A 42-year-old male patient was diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Postoperative complication rates appear to bene t from minimally invasive approaches compared to OIL [3,20,21,23,[25][26][27]. When comparing LIL to open IL, there was a signi cant decrease in wound complications (0% vs 50%) as well as a trend toward lower overall complication rates (20% vs. 70%) [25], concordant with ndings reported by other investigators [16,17]. Similarly, Singh et al [20] reported lower complication rates with RAIL than with open IL (2% vs 17%), consistent with Yu et al [23], who reported that RAIL had fewer postoperative wound complications.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Postoperative complication rates appear to bene t from minimally invasive approaches compared to OIL [3,20,21,23,[25][26][27]. When comparing LIL to open IL, there was a signi cant decrease in wound complications (0% vs 50%) as well as a trend toward lower overall complication rates (20% vs. 70%) [25], concordant with ndings reported by other investigators [16,17]. Similarly, Singh et al [20] reported lower complication rates with RAIL than with open IL (2% vs 17%), consistent with Yu et al [23], who reported that RAIL had fewer postoperative wound complications.…”
Section: Discussionsupporting
confidence: 87%
“…In terms of operative time, while some studies have reported no statistically signi cant difference between minimally invasive and open IL [26,27], most papers reported a longer operative time for minimally invasive surgeries. The operative time for RAIL when excluding reports combining inguinal lymphadenectomy with other procedures (e.g., vulvectomy, pelvic lymph node dissection) was quite variable, ranging from 45 to 279 min [5,17,18,24]. Similarly, various studies reported very heterogeneous results for the operative time of LIL, which ranged between 90 and 240 min [7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…There is not enough evidence regarding the role of the da Vinci robot (Intuitive Surgical, Sunnyvale, USA) in groin node dissection. The approach has never been used for patients with vulval cancer; however, it has been used in patients with melanoma or penile cancer ( 6 , 8 , 10 , 11 , 12 ). We present the possible advantages of such an approach in patients with vulval cancer based on the experience from other specialties or the videoscopic technique ( 13 , 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 Furthermore, ILND is the indicated procedure in regional lymph node management for other kinds cancer of the lower limb with positive nodes such as melanoma, Merkel cell carcinoma, and squamous cell carcinoma (SCC). 2…”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, ILND is the indicated procedure in regional lymph node management for other kinds cancer of the lower limb with positive nodes such as melanoma, Merkel cell carcinoma, and squamous cell carcinoma (SCC). 2 Unfortunately, 10-46% of patients undergoing ILND are subject to complications, even in the most experienced hands. The most common complications reported are: wound dehiscence, cellulitis, skin necrosis, leg edema, and deep vein thrombosis.…”
Section: Introductionmentioning
confidence: 99%